Human antibodies react with an epitope of the human papillomavirus type 6b L1 open reading frame which is distinct from the type-common epitope. - Jenison, S A (1989)
Recombinant proteins encoded by the human papillomavirus type 6b (HPV6b) L1 open reading frame react with sera from patients with condylomata acuminata and also react with rabbit antiserum raised against sodium dodecyl sulfate-disrupted bovine papillomavirus type 1 (BPV1) virions. To map the immunoreactive epitopes, a series of procaryotic expression plasmids was made which contained a nested set of 3' to 5' deletions in the HPV6b L1 open reading frame. The deleted plasmids expressed a set of carboxy to amino terminus truncated fusion proteins. Regions containing the immunoreactive epitopes were mapped by determining which of the deleted fusion proteins retained reactivity with sera in Western immunoblot assays. The coding sequence for a human antibody-reactive linear epitope mapped between HPV6b nucleotide coordinates 7045 and 7087, and the rabbit anti-BPV1-reactive epitope coding sequence mapped between coordinates 6377 and 6454. Synthetic peptides derived from the epitope mapping were reacted with sera in enzyme-linked immunosorbent assay. Human sera reacted with synthetic peptide QSQAITCQKPTPEKEKPDPYK (HPV6b L1 amino acids 417 through 437). Rabbit anti-BPV1 and rabbit antisera raised against HPV16 L1 recombinant proteins reacted with the synthetic peptide DGDMVDTGFGAMNFADLQTNKSDVPIDI (HPV6b L1 amino acids 193 through 220). Human sera which reacted with HPV6b L1 fusion proteins cross-reacted with an HPV11 L1 fusion protein but did not react with fusion proteins encoded by HPV1a, HPV16, or HPV18. Rabbit anti-BPV1 reacted with L1 fusion proteins encoded by all of these HPV types. In contrast to the type-common (rabbit anti-BPV1-reactive) epitope, the human antibody-reactive epitope appears to be relatively HPV type specific.